Hard to Ignore: Impulsive Buyers Show an Attentional Bias in Shopping Situations. (April 2014) - Büttner, Oliver B.; Florack, Arnd; Leder, Helmut; Paul, Matthew A.; Serfas, Benjamin G.; Schulz, Anna Maria
This research focuses on the attentional processes that underlie buying impulsiveness. It was hypothesized that impulsive buyers are more likely than nonimpulsive buyers to get distracted by products that are unrelated to their shopping goal. The study applied a 2 (buying impulsiveness low vs. high) × 2 (shopping vs. nonshopping context) × 2 (product vs. nonsemantic distractors) mixed design. Participants' attention allocation was measured via eye tracking during a visual distraction paradigm. The results support the distraction hypothesis. Impulsive buyers allocated less attention to a focal product than nonimpulsive buyers. The effect was context-specific and emerged only when the task was framed as a shopping situation. The results show that distraction is not limited to attractive products and suggest that it is driven by a general attentional openness for products in shopping situations.